P4_2 Using the Forks: The Energy Yield of a Lightning Bolt - Szczykulska, Magdalena; Watson, Jason John; Garratt-Smithson, Lilian; Muir, Alistair William (Physics Special Topics, 2013)
Lightning may be considered as a potential energy source if the yield is comparable to other renewable energy sources. The energy yield of one strike was evaluated to be 7.5Ã—107 J, where approximately 50 strikes produce a yield equivalent to that of an average wind turbine in a year.